Fluid flow analysis to describe the permeation process along the length of the porous tube. (5th October 2017) - Najmi, H.; El-Tabach, E.; Gascoin, N.; Chetehouna, K.; Lamoot, L.; Falempin, F.
Abstract: The use of a fuel Cell on board of an aircraft enforces the extraction of light species (such as Hydrogen and light hydrocarbons) from the liquid fuel which is stored and used, possibly at temperatures where fuel pyrolysis occurs. Natural porosity of composite material could be used to filtrate the selected species. Hence, the permeability and selectivity of the porous media becomes the key parameter to be measured accurately. This is often determined experimentally in laboratory using disc or cube samples and a perpendicular flow (outlet of the flow is achieved through the porous material). However in realistic configuration composed of tube, additional flow is found through the material tangential to main flow. Previous work has shown that the permeation is not constant all along the length of the porous channel. Permeance of a gas governs the permeation process along the length of the tube, which impacts the selectivity in case of a multispecies flow. In this study, a new permselectivity test bench is developed in order to study the permeance and selectivity all along the length of a porous tube with the help of isolated permeation cells. Pure N2 is used as a fluid at ambient temperature for evaluating the ability and accuracy of the test bench as a function of operating conditions. The effects of different inlet mass flowrate and pressure on the permeation along the tube have been studied. The obtained results of permeation along the length of a porous stainless steel tube are compared and discussed. The values of permeability obtained experimentally are in agreement with the literature data which guarantees the reliability of the test bench and of related measures. Comparison with analytical laws contribute to the investigation and explain the fundamental physics of the permeation process that will be later used to further study the selectivity of porous materials in case of multispecies flow. Highlights: A new permselectivity test bench is developed. To determine the permeance and selectivity along the length of porous channel. The filtration has significant effect on pressure drop inside the tube. Traditional flow equation cannot describe fluid flow inside the porous tube. Point of interaction between the porous flow and main flow is the boundary layer.